2019
DOI: 10.1016/j.ejmech.2019.111655
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of stereo- and regioisomers of amino aryl esters as multidrug resistance (MDR) reversers

Abstract: Stereo-and regioisomers of a series of N,N-bis(alkanol)amine aryl ester derivatives have been prepared and studied as multidrug resistance (MDR) modulators. The new compounds contain a 2-(methyl)propyl chain combined with a 3-, 5-or 7-methylenes long chain and carry different aromatic ester portions. Thus, these compounds have a methyl group on the 3-methylenes chain and represent branched homologues of previously studied derivatives. The introduction of the methyl group gives origin to a stereogenic center an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 73 publications
(61 reference statements)
2
40
0
Order By: Relevance
“…We compared Tariquidar, the latest clinically tested Pgp inhibitor [22], and R-3, a N,N-bis(alkanol) amine aryl ester derivative recently synthesized by our group, with an EC 50 for Pgp similar to Tariquidar [23,24]. Tariquidar is reported to bind to the drug binding pocket of the protein, in particular, to the so-called H-site, which is localized within the inner leaflet of the membrane at 10.5 to 14.5Ǻ apart from the membrane surface [32], and it was suggested that it inhibits Pgp pumping from the cytoplasmic face of the membrane [33].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We compared Tariquidar, the latest clinically tested Pgp inhibitor [22], and R-3, a N,N-bis(alkanol) amine aryl ester derivative recently synthesized by our group, with an EC 50 for Pgp similar to Tariquidar [23,24]. Tariquidar is reported to bind to the drug binding pocket of the protein, in particular, to the so-called H-site, which is localized within the inner leaflet of the membrane at 10.5 to 14.5Ǻ apart from the membrane surface [32], and it was suggested that it inhibits Pgp pumping from the cytoplasmic face of the membrane [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tariquidar is a competitive inhibitor of Pgp [30], while R-3 is not [23], although they both reduced the efflux of doxorubicin through Pgp. To clarify why these two inhibitors of Pgp produced such different effects on ICD, we wondered whether they affected the amount of surface Pgp that we previously identified as an inhibitor of CRT immunogenic functions [19].…”
Section: Pgp Internalization and Degradation Restores Immunogenic Celmentioning
confidence: 96%
See 3 more Smart Citations